Factors associated with visual impairment, disability, and quality of life among elderly people in two welfare homes in Malaysia - Falahaty, Khadijeh (2013)
Visual impairment is one of the leading causes of functional disability in old age. The purpose of this study was to determine factors are associated to visual impairment and assess disability (ADL&IADL) and quality of life among two welfare home residents. A cross-sectional design was employed to determine the factors that are associated with visual impairment among elderly people. A total of 150 subjects were selected by simple random sampling from two welfare homes (Cheras in Selangor, and Seremban) in Malaysia. The socio-demographic variables (age, gender, ethnicity, income), health behavior (smoking) and self-reported medical condition (diabetic, eye disease, hypertension, heart disease, and stroke) were examined in relationship with visual impairment. Instruments used in this study included eye test by Snellen E Chart, ADL & IADL scales and a list of questions about self-reported medical conditions and disease. Descriptive analysis such as mean, standard deviation (SD) and frequency were utilized to describe the characteristics of the respondents. The mean age of respondents was 69 years (SD = 7.31). A chi-square test (p< 0.05) and multiple linear regression (R2=0.64) analyzes were utilized to determine predictors of visual impairment. The effect of visual impairment on disability examined by a bivariate test. Also to determine the effect of disability on quality of life among welfare home residents, independent t test statistic were utilized. The prevalence of visual impairment (46%) and blindness (28%) was in compare to normal vision (26%).Also the prevalence of disability in bathing (53.9%) of ADL and preparation food (88%) of IADL was more in compare to another items .The findings confirmed the socio demographic factors (age, gender, ethnicity, income) health behavior (smoking) and disease (diabetic, eye disease, heart disease,hypertension and stroke) were associated to visual impairment. Visually impaired elderly had more disabilities in ADL and IADL. Moreover the subjects with visual impairment had poorer quality of life than subjects without visual impairment. Health care professionals should be trained to asses and be sensitive to disability issues in old age. Visual impairment should be acknowledged and emphasized in policy and intervention programs are needed to improve quality of life in older Malaysians.